Epidemiological characteristics associated with uptake of pneumococcal vaccine among older adults living in the community in Singapore: Results from the National Health Surveillance Survey 2013. Issue 2 (March 2018) - Ang, Li Wei; Cutter, Jeffery; James, Lyn; Goh, Kee Tai
Aims: In Singapore, pneumococcal vaccination is recommended for the elderly (i.e. those ≥65 years of age) and people with chronic medical conditions. We investigated epidemiological characteristics associated with the uptake of pneumococcal vaccine based on a nationally representative cross-sectional sample of community-living adults aged ≥50 years. Methods: The data were obtained from the National Health Surveillance Survey (NHSS) 2013. Associations between pneumococcal vaccination and sociodemographic and health-related variables were analysed using univariable and multivariable logistic regression models. Results: Among 3672 respondents aged ≥50 years in the NHSS, 7.8% had taken the pneumococcal vaccination. A higher level of education and higher monthly household income were sociodemographic characteristics independently associated with pneumococcal vaccine uptake. Health-related characteristics predictive of pneumococcal vaccine uptake were better self-rated health and having a regular family doctor/general practitioner. Among those who responded to the two questions on vaccinations, 3.9% had been vaccinated against both seasonal influenza and pneumococcal infection, while 11.1% had taken only seasonal influenza vaccination in the past year.Conclusions: There is a need to boost pneumococcal vaccination coverage among community-dwelling older adults. These findings provide insights into reviewing and tailoring public-health strategies and programmes to increase vaccine uptake in at-risk population groups.